(NsO^INENIQ DLQ FORTEPIANO(B:(NW DWUH TOMAH(B.(NtOM (B1: 24 (NPREL@DII I FUGI(B.s (NNOTYs - (N}EDRIN(B.(Nr(B.(Nks ((NmOSKWAs (NmUZYKAs, 2007)
(Nw PERWYJ TOM SO^INENIJ DLQ FORTEPIANO WYDA@]EGOSQTOT^ESTWENNOGO KOMPOZITORA r(B.(Nk(B.(N}EDRINA WO[EL CIKL PREL@DIIJ I FUG(B, (NPOPULQRNYJ WPEDAGOGI^ESKOJ ISPOLNITEL_SKOJ PRAKTIKE(B.s
Keywords: (NFORTEPIANOs